Preparation of a magnetic molecularly imprinted polymer for non-invasive determination of cortisol - Villa, Javier E. L. [UNESP]; Khan, Sabir [UNESP]; Neres, Lucas C. S. [UNESP]; Sotomayor, Maria D. P. T. [UNESP] (Springer Nature, 2021)
This work presents the theoretical design, synthesis, characterization and application of a magnetic molecularly imprinted polymer (Mag-MIP) to quantify cortisol, the main stress biomarker, in urine samples. Density functional theory was used to predict a suitable solvent (acetonitrile) and a functional monomer (methacrylic acid) for MIP synthesis. Under these conditions, the Mag-MIP material was obtained by surface polymerization of modified Fe3O4 nanoparticles synthesized via the polyol method. The materials were characterized by scanning/transmission electron microscopy, infrared spectroscopy, vibrating sample magnetometry and thermogravimetric and Brunauer–Emmett–Teller surface analyses. Additionally, the Mag-MIP binding experiments showed rapid cortisol adsorption (completed in 20 min), Langmuir–Freundlich isotherm and a pseudo-first-order kinetic equation behaviour, and an excellent maximum binding capacity (200 µg g−1). The results were compared to those obtained for the magnetic non-imprinted polymer (Mag-NIP) and showed superior Mag-MIP performance. Selectivity experiments indicated that the Mag-MIP is capable of efficiently capturing cortisol in the presence of potential interfering substances. The Mag-MIP material was then applied to rapid quantitative cortisol extraction from urine samples prior to high-performance liquid chromatography with ultraviolet detection (limit of detection of 4 µg L−1 and recoveries ranging between 92 and 100%). Therefore, the proposed method might be readily implemented for routine non-invasive monitoring of human stress levels and other cortisol-related conditions.
Keywords: DFT; HPLC–UV; Hydrocortisone; Magnetite; MIP